From Judicial Discretion to Maqasid al-Shari'ah Reasoning: The Case of Marriage Dispensation at the Muara Bulian Religious Court, Indonesia - Kurniawan, Ardian; Muhammadromli Samae, Syarif Bin; Arbi, Hamida (Islamic Law and Social Issues in Society, 2025)
This article discusses the application of judicial discretion in marriage dispensation of Decision Number 106/PDT.P/2023/PA.MBL at the Muara Bulian Religious Court based on the perspective of maqāṣid al-sharīʻah. Amid increasing legislative efforts to protect children by raising the minimum marriage age, judicial discretion has become a determining factor in granting or rejecting marriage dispensation applications. Thus, this article aims to analyze how judges interpret and apply the concept of “urgent reasons” in cases involving a 14-year-old prospective bride, explore how judges incorporate principles of maqāṣid al-sharīʻah, particularly the balance between the preservation of lineage (ḥifẓ al-nasl) and the protection of life and intellect (ḥifẓ al-nafs and ḥifẓ al-ʻaql), in their legal considerations, and assess the gap between formal child protection standards and their practical implementation within the religious court system. By using a qualitative research approach with legal document analysis, this article finds that judicial discretion in this case involves an expansive interpretation of “urgent reasons” based on premarital sexual relations, a narrow focus on ḥifẓ al-nasl rather than a holistic assessment of the child's best interests, and significant discrepancies between formal protections and their practical application. These findings highlight a fundamental tension between a preventive approach toward premarital sexual relations and the long-term protection of children's rights within the framework of contemporary maqāṣid al-sharī'ah. This article contributes to a better understanding of the complexities of judicial discretion in child marriage cases and offers insights for improving legal reasoning standards to prioritize child protection in Indonesia.